Long-term correction of hemophilia B through CRISPR/Cas9 induced homology-independent targeted integration. (December 2022) - Chen, Xi; Niu, Xuran; Liu, Yang; Zheng, Rui; Yang, Lei; Lu, Jian; Yin, Shuming; Wei, Yu; Pan, Jiahao; Sayed, Ahmed; Ma, Xueyun; Liu, Meizhen; et al.
Abstract: CRISPR/Cas9-mediated site-specific insertion of exogenous genes holds potential for clinical applications. However, it is still infeasible because homologous recombination (HR) is inefficient, especially for non-dividing cells. To overcome the challenge, we report that a homology-independent targeted integration (HITI) strategy is used for permanent integration of high-specificity-activity Factor IX variant ( F9 Padua, R338L) at the albumin ( Alb ) locus in a novel hemophilia B (HB) rat model. The knock-in efficiency reaches 3.66%, as determined by droplet digital PCR (ddPCR). The clotting time is reduced to a normal level four weeks after treatment, and the circulating factor IX (FIX) level is gradually increased up to 52% of the normal level over nine months even after partial hepatectomy, demonstrating the amelioration of hemophilia. Through primer-extension-mediated sequencing (PEM-seq), no significant off-target effect is detected. This study not only provides a novel model for HB but also identifies a promising therapeutic approach for rare inherited diseases.